Dysfunction of the continent ileostomy: clinical features and bacteriology. Issue 3 (March 1983) - Kelly, D G; Phillips, S F; Kelly, K A; Weinstein, W M; Gilchrist, M J
Abstract : The pathogenesis and treatment of dysfunction of the continent ileostomy was investigated in 12 patients, five of whom had asymptomatic malabsorption and seven of whom had acute complaints. The number of anaerobic bacteria in jejunal aspirates was increased in patients with pouch malfunction (range 10(3) to 10(8)/g aspirate), but the microbiology of ileal effluent and the morphology of the ileal mucosa could not be correlated with dysfunction. Bile acid breath tests and lactose tolerance tests were not, however, reliable indicators of jejunal bacterial overgrowth. The symptoms, the malabsorption, and the number of jejunal and ileal anaerobic bacteria decreased in patients during treatment with metronidazole, implicating overgrowth of anaerobic bacterial flora in the pathogenesis of the syndrome.